Analysis of Village Economic Potential through Public Service Management in BUMDesma Sikompak Governance to Support Food Security in West Limboto District, Gorontalo Regency - Gobel, Lisda Van; Rachman, Ellys; Katili, Andi Yusuf; Alamri, Moh. Rafli; Feriska, Lisa (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the economic potential of villages through public service management in BUMDesma governance with a focus on the principles of good corporate governance which include responsibility, openness, accountability, independence, and fairness. This study uses a qualitative method with a case study approach. Data is collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion/verification. The results of the study show that the application of good corporate governance principles has not been maximized in increasing the business of BUMDesma in accordance with the provisions expected to strengthen the economy of the village community. Similarly, the factors of participation, cooperation, emancipation, and sustainability as determinants of the success of public services have not been carried out optimally due to various obstacles, including the lack of operational costs, government dominance in policy-making, lack of concern from the private sector for the interests of the community, conflicts of interest between stakeholders, and low entrepreneurial knowledge and competence of administrators. The recommendations of this study are the need to increase the capacity of BUMDesma administrators through entrepreneurship training, strengthening collaboration between the government, the private sector, and the community, as well as more transparent and sustainable management of village resources to support food security and the welfare of village communities.